Effect of fracture on gas migration, leakage and CO2 enhanced shale gas recovery in Ordos Basin. (November 2018) - Yang, Sen; Li, Yilian; Zhu, Yan; Liu, Danqing
Abstract: Although the CO2 enhanced shale gas recovery (CO2 -ESGR) has been studied to respond to energy shortages and climate changes, previous studies have not examined the effect of fracture on the process of gas migration and leakage. Therefore, this study presents a 3-D numerical model base on geological data of Ordos basin. The leakage of CH4 happens at the beginning of shale gas production in SGR scenario, and the injection of CO2 in CO2 -ESGR scenario can reduce the leakage of CH4 . The higher CO2 injection rate will promote the leakage of CO2 and prevent the leakage of CH4 in CO2 -ESGR scenario. Higher permeability will make the CH4 gas leak from shale reservoir to aquifer easier and faster in both scenarios, but it can relatively prevent the leakage of CO2 in CO2 -ESGR scenario.